Konsep Manajemen Risiko - A.Royyan (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
The development of the world financial system has led to the increasing importance of the role of professional financial institution management. Financial institutions are institutions that manage financial resources from other parties to be used for more productive activities. Advances in technology, information systems, and market openness at a wider level, for example at the global level, require financial institutions to be more careful in managing their business so as not to fall into losses that can involve many parties. This potential loss can arise from an institution's failure to manage the risks it faces, both financial risk, business risk and systemic risk. Therefore, proper risk management for a financial institution is a must.